Design guidelines for pillar and rib pillar extraction in South African collieries - Beukes, Johannes Stephanus (My University, 2016)
Pillar extraction using 'handgot' methods has been practised in South African collieries fOJ' many years. During the late Sixties pillar extraction with mechanized conventional equipment commenced, and approximately a decade later, continuous miners were introduced into pillar and rib pillar extraction panels. During the years that these mining methods were practised, a vast amount of experience was gained on the various collieries. Problems were experienced by various mines and the management of these mines made numerous alterations to the mining methods with varied degrees of success, Research was 0.150 conducted by COMRO and by V,\ri01l5 mines and mining house". Apart from the recommendations of Salamon and Oravecz (1976) on pillar design in stooping sections, little information has been published and, thus, little is generally available to mine managers, planners and operators to assist them in the layout and design for plllar and rib pillar extraction. A survey of all the pillar and rib pillar practises, past and present, has been conducted for collieries in South Africa and abroad and the successes, failures, problems experienced, changes made to the mining methods and the results of these changes have been documented. The problems and successes experienced, t~ similarities and difference between mines and mining methods, and the research flndlngs have been assessed and evaluated. Design guidelines relevant to the various methods of pillar and rib pillar extraction have been established to improve the safety and performance of pillar extraction operations. These guldellnea ate not intended to be prescriptive but are designed more to bring to the attention of the mine manager, planner and operator those fllctors which should be taken into consideration during the planning and operation \)f a pillar Ot rib pillar extraction panel. In addition to the strata related factors, the economics of the mining method is important to determine if it is beneficial to do secondary ext-action, and also to assist in optimlsing the secondary extraction. The design prlnclplns were therefore appUed to diffcrtmt panel layouts, pillar sizes and extraction sequences to determine the effect on the production costs.
A dissertation submitted to the Faculty of Engineering, University of the Witwatersrand, .tohannesburg, ill fulfilment of the requirements for the degree or Mester of Science in Engineering Johannesburg, 1992
Keywords: Coal mines and mining--Research--South Africa; Pillaring (Mining); Ground control (Mining)